2020
DOI: 10.1016/j.socscimed.2020.113309
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in well-being of parents of individuals with developmental or mental health problems

Abstract: Rationale A large body of work demonstrates the impact of caregiving burden on the well-being of parents of individuals with developmental conditions or mental health problems. However, a relative dearth of research examines this impact longitudinally into parents' older age. Objective. The current study examines (1) longitudinal changes in the effect of having a child with a developmental or mental health problem on parental negative affect, psychological well-being, and somatic symptoms, (2) age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…These results are consistent with previous studies that have illustrated health problems facing caregivers of a child with SPID. 5 Similar to the depression rate mentioned above, the somatization rate in this study is significantly higher than previously found in parents of children with disabilities in general. 31 The results might be related to the severity of the children's disabilities in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are consistent with previous studies that have illustrated health problems facing caregivers of a child with SPID. 5 Similar to the depression rate mentioned above, the somatization rate in this study is significantly higher than previously found in parents of children with disabilities in general. 31 The results might be related to the severity of the children's disabilities in this study.…”
Section: Discussionsupporting
confidence: 86%
“…4 However, studies have demonstrated various challenges, including emotional, health, and economic, faced by caregivers of a child with IDD residing at home. 5 Specifically, studies have shown adverse mental health impacts on the family members, including depression and anxiety, 6 stress, 6 and negative emotions, such as shame and guilt. 7 In addition, parents raising children with IDD at home reported poor physical health, including sleep problems, headaches, and musculoskeletal symptoms.…”
mentioning
confidence: 99%
“…Despite some positive aspects of parenting DD children (Beighton and Wills, 2017), numerous studies have identified psychological and physical costs of caring for DD children (Song et al, 2016(Song et al, , 2018Namkung et al, 2018;Sloan et al, 2020). Yet, extant studies have paid little attention to how the association between having DD children and parents' health can be confounded by early-life factors of parents.…”
Section: Introductionmentioning
confidence: 99%
“…Children with speech impairment are at risk of future academic and socioemotional difficulties, activity limitations and participation restrictions (4). Caring for a child with profound developmental delay, such as speech impairment, could place caregivers at risk of poor mental health status, including symptoms of emotional exhaustion, anxiety, depression, hopelessness, pessimism and possible psychological comorbidities (5)(6)(7)(8)(9). For example, one study in Germany found that the proportion of depressive disorders and anxiety disorders among mothers of children with speech-impairments is 11% and 28%, respectively (10).…”
Section: Introductionmentioning
confidence: 99%